Increased expression of claudin-17 promotes a malignant phenotype in hepatocyte via Tyk2/Stat3 signaling and is associated with poor prognosis in patients with hepatocellular carcinoma - Lemeng Sun; Liangshu Feng; Jiuwei Cui (BMC, 2018)
Abstract Background Hepatocellular carcinoma (HCC) is the second leading cause of cancer death in Asia; however, the molecular mechanism in its tumorigenesis remains unclear. Abnormal expression of claudins (CLDNs), a family of tight junction (TJ) proteins, plays an important role in the metastatic phenotype of epithelial-derived tumors by affecting tight junction structure, function and related cellular signaling pathways. In a previous study, we used a tissue chip assay to identify CLDN17 as an upregulated gene in HCC. Here we aimed to use molecular biology technology to explore the effect of CLDN17 on the malignant phenotype of HCC and the underlying molecular mechanism, with the objective of identifying a new target for HCC treatment and the control of HCC metastasis. Method The expression levels of CLDN17 in HCC tissues and histologically non-neoplastic hepatic tissues were explored by immunohistochemistry. Stable transfection of the hepatocyte line HL7702 with CLDN17 was detected by real-time polymerase chain reaction (PCR), western blotting and immunofluorescence. The impact of CLDN17 on the malignant phenotype of HL7702 cells in vitro was assessed by a Cell Counting Kit-8 (CCK8) assay, a Transwell assay and a wound-healing experiment. Western blotting was utilized to detect the activation state of Tyrosine kinase 2 (Tyk2) / signal transducer and activator of transcription3 (Stat3) pathway. A Tyk2 RNA interference (RNAi) was utilized to determine the impact of the Tyk2/Stat3 signaling pathway on the malignant phenotype of hepatocytes. Results In this work, our research group first found that CLDN17 was highly expressed in HCC tissues and was associated with poor prognosis. In addition, we demonstrated that CLDN17 affected the Stat3 signaling pathway via Tyk2 and ultimately enhanced the migration ability of hepatocytes. Conclusion In conclusion, we confirmed that the upregulated expression of CLDN17 significantly enhances the migration ability of hepatocytes in vitro and we found that the activation of the Stat3 pathway by Tyk2 may an important mechanism by which CLDN17 promotes aggressiveness in hepatocytes.